2019
DOI: 10.1039/c9en00980a
|View full text |Cite
|
Sign up to set email alerts
|

Humic acid regulation of the environmental behavior and phytotoxicity of silver nanoparticles to Lemna minor

Abstract: Results suggest that molecular interaction occurs between AgNPs and HA functional groups and HA can reduce the toxicity of AgNPs to Lemna minor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…Some critical issues emerged from the literature about the protocols proposed by the standardized ISO and OECD guidelines. Methodologies and conditions are not always suitable for the optimal application of ecotoxicological tests based on freshwater plants (e.g., Cairns and Niederlehner, 1995 ; Navarro et al 2002 ; Gubbins et al 2011 ; Pereira et al 2018 ; Ding et al 2019 ) mainly due to the following limitations: Ecosystem complexity . Most of these guidelines refer to experimental tests carried out exclusively under controlled laboratory conditions; this obviously involves some problems (e.g., short time frame, small scale, lack of synergic effects, and complexity of interaction found in nature) that restrict the capability to extrapolate the real status of a natural system from controlled experiments (Carpenter 1996 ; Petersen et al 1997 ; Schindler 1998 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some critical issues emerged from the literature about the protocols proposed by the standardized ISO and OECD guidelines. Methodologies and conditions are not always suitable for the optimal application of ecotoxicological tests based on freshwater plants (e.g., Cairns and Niederlehner, 1995 ; Navarro et al 2002 ; Gubbins et al 2011 ; Pereira et al 2018 ; Ding et al 2019 ) mainly due to the following limitations: Ecosystem complexity . Most of these guidelines refer to experimental tests carried out exclusively under controlled laboratory conditions; this obviously involves some problems (e.g., short time frame, small scale, lack of synergic effects, and complexity of interaction found in nature) that restrict the capability to extrapolate the real status of a natural system from controlled experiments (Carpenter 1996 ; Petersen et al 1997 ; Schindler 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the outputs obtained do not fully reflect the actual harmful effects of tested contaminants on plants in nature. For example, the toxic effects of silver nanoparticles (AgNPs) on Lemna minor (Ding et al 2019 ) are mitigated by the presence of natural suspended substances such as humic acids (HA). HA appear to reduce the absorption capacity of AgNPs in Lemna , therefore limiting the phytotoxical effects in the plant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is the case of molecules with a high reduced sulfur content that bind metal ions with high affinity [149]. The toxicity of AgNPs for both microbes and non-target species has been shown to decrease following the addition of molecules rich in thiol groups in solution, such as natural organic matter or cysteine [18,[150][151][152].…”
Section: Role Of the Surface Coating In Agnps Ecotoxicitymentioning
confidence: 99%
“…Removal efficacy and ecotoxicity are tested in parallel in order to obtain best adsorption performances with no risk for the exposed organisms (Figure 4). following the addition of molecules rich in thiol groups in solution, such as natural organic matter or cysteine [18,[150][151][152]. Several studies have assessed the toxicity of sulfur functionalized AgNPs, and always reported a reduction in toxicity compared to pristine AgNPs.…”
Section: Ecosafe By Design Approachmentioning
confidence: 99%